EFFECT OF MORINGA OLEIFERA ON LEVEL OF PROLACTIN AND BREAST MILK PRODUCTION IN POSTPARTUM MOTHERS - Yuni Sulistiawati; Ari Suwondo; Triana Sri Hardjanti; Ariawan Soejoenoes; M. Choiroel Anwar; Kun Aristiati Susiloretni (Belitung Nursing Journal, 2017)
Background: Breastfeeding among postpartum mothers has been a problem due to low milk supply. As a result, mothers often decide to give formula milk or other additional foods, which may affect infant’s growth and development. Objective: This study aims to investigate the effect of moringa oliefera on the levels of prolactin and breast milk production (baby’s weight and sleep duration) in postpartum mothers. Methods: Quasi-Experimental study with non-equivalent control group design. There were 30 respondents recruited by purposive sampling, consisted of 15 respondents in intervention group and 15 respondents in the control group. This study was conducted from November until December 2016 in Four Midwives Independent Practice (BPM) in the working area of the Health Center of Tlogosari Wetan Semarang. Data were analyzed using Independent t-test. Results: Findings showed that there was a mean difference of prolactin level in the intervention group (231.72 ng / ml) and the control group (152.75 ng / ml), and a significant effect on increasing the levels of prolactin (p = 0.002). The mean of baby’s weight in the intervention group was 3783.33 grams and in the control group was 3599.00 grams. However, there was no significant effect of moringa oleifera on baby’s weight (p = 0.313> 0.05), while the mean difference on sleep duration was 128.20 minutes in the intervention group and 108.80 minutes in the control group. There was a significant effect on baby’s sleep duration (p= 0.000). Conclusion: There were significant effects of moringa oleifera on mother’s prolactin and sleep duration of the baby. However, there was no significant effect on baby’s weight. Thus, it can be suggested that moringa oleifera can be used as an alternative treatment to increase breast milk production and prolactin hormones. Midwives should promote the benefits of moringa leaves as one of alternative supplements.